THE EFFECT OF THE APOS-BASED LEARNING FOR SELF-CONFIDENCE AND MATHEMATICS LEARNING ACHIEVEMENT - Nasruddin; Palobo, Markus (International Journal of Research -GRANTHAALAYAH, 2023)
The purpose of this study was to determine the impact of applying an APOS-based learning model on student self-confidence and mathematics learning performance. This research is an experimental study by Posttest Only Control Design. The location of this research is SMP PGRI ubuntudatu. The population of this study is class VII students. Sampling using the targeted sampling technique was continued using the cluster random sampling technique and samples were taken as VIIA as the control class and VIIB as the experimental class. The data collection techniques used are observation and testing. Data were analyzed descriptively and speculatively. Hypothesis testing by independent-samples t-test. As a result of our research, we found the following: 1) APOS-based learning model has a positive impact on student confidence. This effect was seen in explaining observations in experimental classes, indicating that student self-confidence was more likely to improve at each meeting than in control classes. 2) APOS-based learning models have a positive impact on class math learning performance. Effects are indicated by the obtained t-test results. From this, we can conclude that the APOS-based learning model has a positive impact on mathematics learners' confidence and performance.